Elites and ilustrados in Philippine culture - Hau, Caroline S. 1969- (Ateneo de Manila University Press, 2017)
This book examines how Filipino literature has intervened in the intellectual and popular debates on the historical origins, ascendancy, power, and legitimacy of the elites. Writers like Jose Rizal, Nick Joaquin, Ninotchka Rosca, Miguel Syjuco, and Ramon Guillermo are unsparing in their criticism of elite authorship of the Philippines' past and present woes while seeking to recuperate the critical stance represented by the ilustrado. The book highlights a number of figures--the "middle sector" or "middle element" in Manila and other urban areas, Manila men and musicians, overseas Filipino workers, intellectuals, and Fil-foreigners--whose emergence as social forces points to the ongoing redefinition of the elites and the transformation of Philippine society, politics, and economy.-- Provided by publisher.